Mineral trioxide aggregate endodontic revascularization of nonvital anterior tooth - Tanu Priya Sonkar; Naiya Pathak; Swarup Shetty; Amey J Rathi; Azhar Mohammed; Prashant Viragi (Journal of International Clinical Dental Research Organization, 2022)
Context: Management of nonvital immature teeth requires careful management due to higher risk of root fracture. Aims: The aim of this study was done to evaluate the mineral trioxide aggregate (MTA) endodontic revascularization of permanent nonvital anterior tooth. Materials and Method: Forty patients in the age group of 18–30 years were included in the study. MTA revascularization procedure was done on immature necrotic upper anterior tooth with the presence or absence of periapical condition. The success was assessed with root lengthening, healing, apical closure, and dentinal wall thickness. Age group 18–23 years comprised 12 males and 10 females and 24–30 years had 10 males and 8 females. In 20% of cases, good healing and 80% had excellent healing were seen. Statistical Analysis Used: The obtained data were statistically evaluated using Mann–Whitney U-test for the comparison. Significance of the study was labeled at 0.05, highly significant at 0.01. Results: Mann–Whitney U-test showed a significant difference (P < 0.05). Twenty percent of teeth had fair, 30% had well, and 50% had excellent root lengthening. Apical closure was fair in 40%, good in 20%, and excellent in 40% teeth. Dentinal wall thickening was fair in 35%, good in 40%, and excellent in 25%. Conclusions: A successful revascularization procedure in nonvital permanent anterior teeth was seen both clinically and radiographically in terms of apical closure, greater healing, improved dentinal wall thickening, and root lengthening.